Factors Affecting Initial Intimate Partner Violence–Specific Health Care Seeking in the Tokyo Metropolitan Area, Japan. (September 2014) - Kamimura, Akiko; Bybee, Deborah; Yoshihama, Mieko
This study examined the factors affecting a women's initial intimate partner violence (IPV)-specific health care seeking event which refers to the first health care seeking as a result of IPV in a lifetime. Data were collected using the Life History Calendar method in the Tokyo metropolitan area from 101 women who had experienced IPV. Discrete-time survival analysis was used to assess the time to initial IPV-specific health care seeking. IPV-related injury was the most significant factor associated with increased likelihood of seeking IPV-specific health care seeking for the first time. In the presence of a strong effect of formal help seeking, physical and sexual IPV were no longer significantly related to initial IPV-specific health care seeking. The results suggest some victims of IPV may not seek health care unless they get injured. The timing of receiving health care would be important to ensure the health and safety of victims.